A study on the effects of the slope on the critical velocity for longitudinal ventilation in tilted tunnels. (July 2019) - Li, J.; Li, Y.F.; Cheng, C.H.; Chow, W.K.
Highlights: Effect of slope on critical velocity in a tilted tunnel was studied numerically. A 1:8 reduced-scale tilted tunnel model was also built for experimental studies. Downhill longitudinal ventilation to suppress smoke backlayering is considered. The grade correction factor is found to be dependent on the slope in a linear manner. Values of critical velocity in this study are compared with two other models. Abstract: Motivated by controversy of the grade correction factor in the critical velocity model recommended in most tunnel design codes, the effect of slope on the critical velocity in a tilted tunnel was studied by simulation and experimental methods. A 1:8 reduced-scale tilted tunnel model was built for the experimental studies. When a tunnel is tilted, smoke movement is asymmetrical about the fire source due to buoyancy along the longitudinal tunnel axis. In this paper only the worse scenario of downhill longitudinal ventilation to suppress smoke back-layering uphill is considered. Both the simulation and experimental results in the present study show that the grade correction factor, referred to the critical velocity for horizontal tunnel in Danziger and Kennedy's model, depends on the slope in a linear manner. The values of the critical velocity in the present study agree well with those predicted by the model of Wu and Bakar (2000), but are somewhat higher than the values predicted by the model of Danziger and Kennedy (1982).